2006
DOI: 10.1007/s10803-006-0141-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral Human Immunoglobulin for Children with Autism and Gastrointestinal Dysfunction: A Prospective, Open-Label Study

Abstract: Immunoglobulin secretion onto mucosal surfaces is a major component of the mucosal immune system. We hypothesized that chronic gastrointestinal (GI) disturbances associated with autistic disorder (AD) may be due to an underlying deficiency in mucosal immunity, and that orally administered immunoglobulin would be effective in alleviating chronic GI dysfunction in these individuals. In this pilot study, twelve male subjects diagnosed with AD were evaluated using a GI severity index (GSI) while receiving daily do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 43 publications
0
53
0
2
Order By: Relevance
“…This was primarily due to the large improvement in the placebo group Sandler et al 2000). A prospective, open-label, pilot study of oral, human immunoglobulin demonstrated potential as a possible treatment for children with GI dysfunction associated with autism who had failed traditional medical treatment (Schneider et al 2006). Based upon those preliminary results, this large, randomized, placebo-controlled trial was conducted to examine the effects of oral immunoglobulin in subjects with GI dysfunction and autism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was primarily due to the large improvement in the placebo group Sandler et al 2000). A prospective, open-label, pilot study of oral, human immunoglobulin demonstrated potential as a possible treatment for children with GI dysfunction associated with autism who had failed traditional medical treatment (Schneider et al 2006). Based upon those preliminary results, this large, randomized, placebo-controlled trial was conducted to examine the effects of oral immunoglobulin in subjects with GI dysfunction and autism.…”
Section: Discussionmentioning
confidence: 99%
“…Patients unable to swallow capsules were allowed to open the capsules and sprinkle the powder in liquid or on food. The dosing was based on results from an uncontrolled pilot study (Schneider et al 2006) showing what appeared to be some efficacy and a sustained effect with a 420 mg/day dose of IGOH. A review of the literature suggested that we could expect up to 70% of the IGOH to survive functional and intact through the GI tract.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors suggested that several environmental factors may trigger the autoimmunity seen in children with autism. Schneider et al (2006) found some improvement in chronic GI dysfunction in autistic patients when immunoglobulin was administered orally. The authors postulated that the oral administration of immunoglobulin helped to address an underlying deficiency in the mucosal immunity in these autistic individuals.…”
Section: Mucosal Immunitymentioning
confidence: 96%
“…Schneider et al [102] administered oral immunoglobulin in a pilot study with 12 male ASD subjects, considering the chronic GI disturbances in ASD due to an underlying deficiency in mucosal immunity. By the fourthweek assessment, 50% of subjects had improvements in GI symptoms.…”
Section: Oral Immunoglobulinmentioning
confidence: 99%